2019
DOI: 10.5226/jabmech.8.27
|View full text |Cite
|
Sign up to set email alerts
|

On the interference of vorticity and pressure fields of a minimal fish school

Abstract: In collective swimming, vorticity and pressure fields near a fish may be modified through hydrodynamic interactions between fish, and eventually influence swimming performance. We developed a three-dimensional (3D) computational approach and implemented a parametric study to: 1) make comparisons of the vorticity and pressure fields topology between a single fish and a pair of fish; 2) investigate the change of vorticity and pressure fields topology by varying the relative position and phase shift between the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…(d) Multi-blocked computational grid system consists of local fine-scale body-fitted grids (dimension: 121 × 97 × 20) plus a large stationary global grid (dimension: variant). Reprinted from [35] under a CC BY license, with permission from the Society of Aero Aqua Bio-mechanisms, original copyright 2019.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(d) Multi-blocked computational grid system consists of local fine-scale body-fitted grids (dimension: 121 × 97 × 20) plus a large stationary global grid (dimension: variant). Reprinted from [35] under a CC BY license, with permission from the Society of Aero Aqua Bio-mechanisms, original copyright 2019.…”
Section: Methodsmentioning
confidence: 99%
“…(a) δx = 0.2 L , δy = 1.25 L , δϕ = 0; (b) δx = 0.5 L , δy = 0, δϕ = T /2. For more examples of the wake topology, see [35]. …”
Section: Introductionmentioning
confidence: 99%
“…Conceptually, the setup with two swimmers that we study in the present paper is one of the simplest model realizations of the minimal school [24,25] and has been designed to examine the complex flow dynamics that arises due to the undulation kinematics of the two swimmers. Recent experiments on real fish in a swimming channel with imposed velocity have shown that fish favor a synchronized kinematics with their nearest neighbors as the swimming speed of the school increases [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Halsey et al [14] examined how water turbulence affected the tail beat 34 frequency of sea bass Dicentrarchus labrax swimming in schools of different size. They 35 reported a trend for attenuation of energy advantages which they explained by frequent 36 short-term changes in fish position mediated by the turbulence. At the same time, they 37 recognized that turbulence could modify the relationship between tail beat frequency 38 and rate of oxygen consumption.…”
mentioning
confidence: 99%
“…(a) δx = 0.2L, δy = 1.25L, δφ = 0; (b) δx = 0.5L, δy = 0, δφ = T /2. For more examples of the wake topology, see [35].…”
mentioning
confidence: 99%